2013
DOI: 10.1007/s00011-013-0605-4
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial infarction causes inflammation and leukocyte recruitment at remote sites in the myocardium and in the renal glomerulus

Abstract: Rationale and ObjectiveAcute myocardial infarction (AMI) results in the recruitment of leukocytes to injured myocardium. Additionally, myocardium remote to the infarct zone also becomes inflamed and is associated with adverse left ventricular remodelling. Renal ischaemic syndromes have been associated with remote organ inflammation and impaired function. Here, we tested the hypothesis that AMI results in remote organ (renal) inflammation.MethodsMice were subjected to either AMI, sham procedure or no procedure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 55 publications
3
62
0
Order By: Relevance
“…Monocytes are the key players in this inflammatory damage and mediate a negative effect on myocardial remodelling. Furthermore, remote organ inflammation is evidenced by the upregulation of VCAM-1 in renal glomeruli and by the recruitment and infiltration of leukocytes throughout the kidney 24 h following myocardial infarction (9) . Karasawa et al showed that the inflammatory subset of peripheral monocytes accumulates in injured renal tissue and contributes to renal damage.…”
Section: Discussionmentioning
confidence: 99%
“…Monocytes are the key players in this inflammatory damage and mediate a negative effect on myocardial remodelling. Furthermore, remote organ inflammation is evidenced by the upregulation of VCAM-1 in renal glomeruli and by the recruitment and infiltration of leukocytes throughout the kidney 24 h following myocardial infarction (9) . Karasawa et al showed that the inflammatory subset of peripheral monocytes accumulates in injured renal tissue and contributes to renal damage.…”
Section: Discussionmentioning
confidence: 99%
“…Summed FDG score was 19 (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) and correlated significantly with the global scores for LE (ρ=0.54; P=0.04; Figure 3A) and edema (ρ=0.76; P=0.002; Figure 3B). Consistently, the mean FDG score was significantly elevated in segments with LE compared with those without In patients with chronic MI, a reverse pattern was observed.…”
Section: Regional Glucose Utilizationmentioning
confidence: 91%
“…to a lesser degree, 7,13 providing a rationale for remote remodeling. 14 But the use of FDG is complicated by the fact that its uptake may also reflect the presence of ischemically compromised, viable myocytes after AMI.…”
Section: Circ Cardiovasc Imagingmentioning
confidence: 99%
See 2 more Smart Citations